Progress in the Treatment of HIV-Associated Lymphoma When Combined With the Antiretroviral Therapies - Wang, Chaoyu; Liu, Jun; Liu, Yao (Frontiers in Oncology, 2022)
With the wide use of combination antiretroviral therapy (cART), the life expectancy of HIV-infected individuals drastically improved. However, HIV infection and HIV-associated cancers were the most common causes of death in the HIV-infected populations. The HIV-associated cancers are divided into acquired immune deficiency syndrome (AIDS)-defining and non-AIDS-defining cancers based on the incidence among the HIV-infected patients. Among HIV-associated cancers, acquired immune deficiency syndrome-related lymphoma (ARL) is still the most common condition and the leading cause of HIV/AIDS-related deaths. Diffuse large B-cell lymphoma (DLBCL) and Burkitt’s lymphoma (BL) are the most common subtypes of the ARL. Although Hodgkin’s lymphoma (HL) is not considered as an AIDS-defining cancer, incidence of HL in HIV-infected individuals is higher than the general population. The review summarizes the new progress in the treatment of HIV-associated lymphoma.